2023
DOI: 10.3390/su15076232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Stress on Growth, Proline and Mineral Content in Native Desert Species

Abstract: Implementing large-scale restoration programs requires in-depth understanding about the salinity tolerance of native species, especially in the Arabian Peninsula where salinity is one of the most serious problems. Seedlings of four native species, namely Vachillea pachyceras, Haloxylon salicornicum, Rhanterium epapposum, and Farsetia aegyptia, were subjected to different salinity treatments (1.6 (control), 3, 5, 7, and 10 dS/m). Survival, growth performance, biomass and proline accumulation were assessed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Abdelhamid et al (2013) reported that proline treatment through foliar spraying increased P and K concentrations while decreasing Na concentration under salt stress to bean (Phaseolus vulgaris L.) plants. Suleiman et al (2023) studied native desert plant species under saline conditions and found that proline accumulation increased with increasing salinity level. In our study, the lowest proline level was obtained from the 30 mM CaCl2 treatment, while the highest values were obtained from the 90 mM NaCl treatment, when compared to the control group.…”
Section: Proline Contentmentioning
confidence: 99%
“…Abdelhamid et al (2013) reported that proline treatment through foliar spraying increased P and K concentrations while decreasing Na concentration under salt stress to bean (Phaseolus vulgaris L.) plants. Suleiman et al (2023) studied native desert plant species under saline conditions and found that proline accumulation increased with increasing salinity level. In our study, the lowest proline level was obtained from the 30 mM CaCl2 treatment, while the highest values were obtained from the 90 mM NaCl treatment, when compared to the control group.…”
Section: Proline Contentmentioning
confidence: 99%